ZEMSTVO ELECTIONS IN POLTAVA GUBERNIYA IN 1865–1889 - A. I. Kozachenko (Russian Journal of Economics and Law)
Objective: to reveal the common trends of carrying out zemstvo elections in 1865–1889 and their peculiarities in Poltava guberniya. Methods: The methodological basis of the historical-legal research of zemstvo elections legislation and their results are the abstract-logical, systemic-structural and comparative-legal methods of scientific research. Results: According to the Statute of guberniya and uyezd zemstvo establishments of 1864, zemstvo elections were qualification ones, not universal, not equal, indirect by peasants’ curia, were carried out by open voting. The prevailing trend in chang ing the zemstvo elections system was the government’s pursuit to discredit the zemstvo elections system of 1864, attempts to limit peasants’ particpation and create conditions for electing nobility as town councillors. The main participants of election process on Poltava guberniya territory in 1865–1889 were the zemstvo nobility groups. Competitve struggle between them promoted the development of zemstvo self-government. Scientific novelty: For the first time in historical-legal science zemstvo elections are resaerched with the help of documentary materials of Poltava zemstvo and publications of Poltava zemstvo clerks, which were not earlier used in scientific research. Practical value: using the historical experience of zemstvo self-government with the objective to improve the existing system of local self-government.